THE ESCAPISM OF ADVENTIST ECOTHEOLOGY UNDER THE SHADOW OF MONOVALENT HERMENEUTICS AND ANTHROPO-THEO-ESCHATOLOGY - Rumbay, Uriah; Rumbay, Christar Arstilo (12th International Scholars Conference 2025, 2026)
Environmental issues are among the most urgent global challenges of the 21st century, requiring not only technical solutions but also multidisciplinary approaches. In this context, eco-theology emerges as a vital alternative, linking faith with ecological responsibility. However, this study argues that the Seventh-day Adventist (SDA) Church has not given sufficient or serious attention to ecological issues, either theologically or practically. Environmental engagement within Adventism remains largely sloganistic, lacking deep reflection in its doctrines and praxis. This research contends that the absence of serious SDA involvement in environmental concerns stems not merely from a lack of awareness or information, but from theological and hermeneutical problems. Using a qualitative descriptive-argumentative approach, this study analyzes the biblical interpretive foundation within Adventism, which is still heavily dominated by a monovalent hermeneutic—that is, an emphasis on a single, objective meaning derived from a historical-grammatical method. This hermeneutic tends to be apologetic and closed to more dynamic, contextual readings, including those focused on ecological issues. Furthermore, the church’s anthropocentric and theocentric eschatology, which emphasizes Christ’s second coming and the future new earth, reinforces an escapist attitude toward the present world. As a result, the church prioritizes final salvation over ethical engagement with current global issues. This study recommends a paradigm shift in Adventist hermeneutics toward an eco-hermeneutical approach that can integrate Adventist faith with ecological responsibility in a theological, prophetic, and contextual manner. In doing so, the church may become a spiritually relevant actor in responding to the global ecological crisis with transformative impact.